Amendments to the Revised Municipal Code of Chicago of 1905 and New General Ordinances Ch. 45, Art. I p.40 § 1562 (1905) - (:unkn) unknown (General Publisher, 1905)
Prohibited carry of firearms, throwing stones, or other missiles within any of the parks, public playgrounds, or beaches within the city.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES